A diagnostic investigation and a corrective model for implementing change in response to innovation - Álvarez A., Humberto R.; Crowe, Thomas J. (Missouri - Columbia : University of Missouri, Columbia, 2002)
Organizational change can be described as a series of activities oriented towards modifying behaviors and structures within the organization. These series of activities are interconected internaly and externally influence decision and processes in the organization. There has been significant amount of work in organizational change, using both behavioral and systemic approaches. Moreover it has been argued that research in change processes and outcomes to detec how organizational change contex, content and processes involved in a change initiative. This research proposes a model to help organizations implement change initiatives with an increased likelihood ofsuccess. The influence of Model for Organizational Change - IMOC - was developed with the hope of better demostraing the dynamics that take place in the organization by using a systems engineerig view. As an excercise to verify the relationsips tha goven IMOC a system dynamic simulation model was partially developed. The dynamic simulation confirmed the impact of varables such as empleoyees and management participation, enviroment and delay in implementig policies on the level of ressitence to change existing in the organization.
A Dissertation Present To The Faculty Of The Graduate School.
Include bibliography.
Keywords: Industrial Engineering